PENINGKATAN KEMAMPUAN MOTORIK KASAR ANAK USIA NIDI MELALUI PERMAINANTRADISIONAL PADA KELOMPOK B TK ISLAM SILMI SAMARINDA - Nurwati - Nurwati (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Widya Gama Mahakam Samarinda, 2019)
Gross motoric ability is one aspect of development carried out in early childhood. Kindergarten learning program is a whole unit that is developed through themes and sub-themes in the process of interacting with kindergarten children at learning resources by playing in the game environment or better known as the area or center. The increase in gross motoric skills of kindergarten children is generally carried out outside the classroom with the development of learning programs according to the curriculum that must be developed according to the level of achievement of children from one stage to the next stage through a game. This study aims to improve the Gross Motoric Ability of Early Childhood through Traditional Games in Group B of Silmi Samarinda Islamic Kindergarten. This research was conducted in Group B of TKIslam Silmi Samarinda. The method used in this study is Classroom Action Research (CAR), carried out three times in one cycle with four stages: (1) Planning, (2) actions, (3) observations and (4) reflection. The research subjects were 20 students aged 5-6 years. The research data was obtained from the collection of instruments through observation, field notes and documentation. The results of the study increased the gross motoric skills of children after analyzing the data on four aspects of assessment, namely; jumping, body balance, agility, and flexibility seen these four aspects have different levels of difficulty where the aspects of jumping and body balance as a whole are able to do so, while the aspects of agility and flexibility of most children have a low ability. But the overall gross motor skills of the children in the pre-study reached 64%, the first cycle reached 70%, the second cycle reached 801% and the third cycle 90%. Traditional game method is a very appropriate method applied in increasing gross motor skills of children aged 5-6 years or group B.